The Role of Marketing Orientation as an Intermediate Variable in the Relationship between Growth Strategy and Marketing Performance: Applying to Egyptian Insurance Companies - Al-Dagher, Zainab Adly (The Arab Journal of Administration, 2024)
The research dealt with identifying the role of marketing orientation as a mediating variable in the relationship between growth strategy and marketing performance by applying to Egyptian insurance companies, as it sought to answer the following question: “What is the impact of the role of marketing orientation as a mediating variable on the relationship of growth strategy and marketing performance in Egyptian insurance companies”. In order to answer this question, the researcher designed a survey list that included (44) items to collect primary information from the study sample consisting of (280) individuals, and in light of this, data is collected and analyzed and research hypotheses tested using the SPSS statistical package for social sciences. After conducting the analysis of the research data and its hypotheses, the research reached several results, the most important of which are:- There is a significant effect of the growth strategy (integration strategy, diversification strategy, focus strategy) on the marketing performance (profitability, market share) of Egyptian insurance companies at the level of significance (α≤0.05). There is a significant effect of the strategy of focusing on the marketing performance in the presence of the marketing orientation in the Egyptian insurance companies at the level of significance (α≤0.05).